229k views
5 votes
F(4) if f(x) = 3x - 1

User Everlasto
by
4.9k points

2 Answers

5 votes
beeeeeeeeeeeeeeep hope it helps
User Koekenbakker
by
5.4k points
4 votes

Simply substitute the value of 3 given. In other words,

f(3) is the function of

f(x), however, in this case, x is 3

f(3)=3(3)−4

Distribute 3 through the parenthesis

f(3)=9−4

Simplify

f(3)=5

User Dezzie
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.